Speed adjustment characteristics analysis for electromechanical transmission system of coal shearer - YI Yuan-yuan; QIN Da-tong (工程科学学报)
To investigate the feasibility of speed adjustment of the drum and the influence of speed adjustment on the dynamic performance of the transmission system, a cutting-haulage coupled model of the electromechanical transmission system of the coal shearer was established using MATLAB/Simulink. Then, considering reliable operation and efficient production, four types of speed adjustment schemes were formulated for the overload conditions of the cutting unit. The method of selecting the speed adjustment scheme was proposed according to the target cutting thickness, while the motor current was chosen as a feedback signal to calculate the target cutting thickness. Lastly, the electromechanical dynamic characteristics of the system corresponding to different adjustment schemes were simulated and compared. The results show that when the overload ratio of the cutting motor is small, using the drum speed adjustment scheme can not only reduce the system load, but also enable the coal-mining productivity to not be affected. Conversely, the system reliability can be improved when the haulage speed adjustment scheme is used, and using the haulage-drum sequential speed adjustment scheme can lead to high productivity.